Silver-Promoted Regioselective Oxidative Decarboxylative C–H Alkylation of Phenanthridines with Carboxylic Acids - Huang, Tianyin; Yu, Yang; Wang, Hui; Lin, Yifan; Ma, Yurui; Wang, Haoyu; Ding, Chang-Hua; Xiao, Junjie; Xu, Bin (Synthesis, 2020)
A novel oxidative decarboxylative C–H alkylation of phenanthridines with carboxylic acids was developed for the efficient synthesis of multi-substituted phenanthridine derivatives. The given method features easy availability of starting materials, high regioselectivity, and mild conditions. Furthermore, a one-pot synthesis of multi-substituted phenanthridine derivatives was realized by the reaction of biphenyl isocyanides and carboxylic acid.
Keywords: phenanthridine; decarboxylation; silver acetate; C–H alkylation; potassium persulfate; late-stage modification